Strategic repositioning of university libraries through no-code prototyping and cognitive metaphor: a case study at the Federal Institute of Education, Science and Technology of Ceará (IFCE), Iguatu campus (Research, Society and Development, 2026)
Despite technological advancements, university libraries face persistent operational difficulties related to the physical location of the collection and inventory accuracy. This study analyzes the strategic management of these units through the lens of service branding and operational efficiency. The main objective is to investigate how the integration between a "Neighborhood Metaphor" and an independent technological artifact, developed on a no-code platform, can mitigate informational disintermediation. Methodologically, the research is characterized as a qualitative case study, descriptive in nature and propositional in character, based on the technical validation of a prototype for the IFCE Campus Iguatu library (with a collection of 11,114 records). The results demonstrate that the transposition of decimal logic into intuitive spatial coordinates has the potential to reduce the user's cognitive effort and optimize real-time asset auditing. It is concluded that branding, when embodied by UX (User Experience) solutions, strengthens institutional sustainability and repositions the library as a vital strategic asset.